(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
The present study investigates the influence of a magnetic field on the three-dimensional movement of Casson nanofluid over a rotating, stretchable surface embedded in a porous medium. The effects of various parameters on the fluid dynamics are also analyzed. The governing nonlinear partial differential equations (PDEs) representing the fluid flow problem are converted into dimensionless ordinary differential equations (ODEs) using similarity transformations. These resulting ODEs are then solved numerically using the R. K. based Shooting method. The impact of various parameters on the flow profiles is illustrated through graphical representations. It is observed that the velocity profile decreases with an increase in the magnetic field number. Moreover, higher non-Newtonian parameter values lead to an increase in the primary velocity while showing a decreasing trend in the secondary velocity. Journal of Naval Architecture and Marine Engineering, 22(1), 2025, pp. 41-47